Child care center staff composition and early child development - Nina Drange; Marte Rønning (Statistics Norway, Research Department, 2017)
We estimate effects of child care center staff composition on early child development. During the years our data covers, child care centers in Oslo were oversubscribed, and child care slots were allocated through a lottery. This allow us to explore how staff education, experience and stability, as well as proportion of male and immigrant staff, affect the cognitive development of children whose parents initially applied for the same center(s), but where children got offers from different institutions. We find that children who get their first offer of child care enrollment in a child care center with a higher share of male staff, perform better on tests in language and mathematics in the early years of school.
Keywords: I21; J13; 330; Child care quality; child development